Functional Studies of β-Glucosidases of Cytophaga hutchinsonii and Their Effects on Cellulose Degradation - Bai, Xinfeng; Wang, Xifeng; Wang, Sen; Ji, Xiaofei; Guan, Zhiwei; Zhang, Weican; Lu, Xuemei (Frontiers in Microbiology, 2017)
Cytophaga hutchinsonii can rapidly digest crystalline cellulose without free cellulases or cellulosomes. Its cell-contact cellulose degradation mechanism is unknown. In this study, the four β-glucosidase (bgl) genes in C. hutchinsonii were singly and multiply deleted, and the functions of these β-glucosidases in cellobiose and cellulose degradation were investigated. We found that the constitutively expressed BglB played a key role in cellobiose utilization, while BglA which was induced by cellobiose could partially make up for the deletion of bglB. The double deletion mutant ΔbglA/bglB lost the ability to digest cellobiose and could not thrive in cellulose medium, indicating that β-glucosidases were important for cellulose degradation. When cultured in cellulose medium, a small amount of glucose accumulated in the medium in the initial stage of growth for the wild type, while almost no glucose accumulated for ΔbglA/bglB. When supplemented with a small amount of glucose, ΔbglA/bglB started to degrade cellulose and grew in cellulose medium. We inferred that glucose might be essential for initiating cellulose degradation, and with additional glucose, C. hutchinsonii could partially utilize cellulose without β-glucosidases. We also found that there were both cellulose binding cells and free cells when cultured in cellulose. Since direct contact between C. hutchinsonii cells and cellulose is necessary for cellulose degradation, we deduced that the free cells which were convenient to explore new territory in the environment might be fed by the adherent cells which could produce cello-oligosaccharide and glucose into the environment. This study enriched our knowledge of the cellulolytic pathway of C. hutchinsonii.